OVER AGAIN: POTENTIAL NOVEL PERSPECTIVES FROM LEXICAL CONCEPTS & COGNITIVE MODELS THEORY - Long, Do Tuan (VNU Journal of Foreign Studies; Vol 34 No 4DO - 10.25073/2525-2445/vnufs.4283, 2018)
This article aims at analyzing the approaches by different authors to the English preposition over, showing their strengths and weaknesses . We then try to apply the theoretical constraints of Lexical concepts & Cognitive Models (hereafter: LCCM) to treat over from a novel perspective. Seth (2009) can describe the pragmatics of over in stances of use, but he fails to present the distinct senses of the word. Though Lakoff’s framework of Full-Specification could figure out the distinct senses of over , the vast proliferation of senses and a lack of methodological constraints make the approach inappropriate in certain cases. Other works by Kreitser (1997), Tyler & Evans (2003), Deane (2005) and Maria Brenda (2014) could, to certain extent, fill the gaps of Lakoff, but they have failed to address the issue of combining both the linguistic (parametric) and the non-linguistic (analogue) representations in analyzing the semantics of over . It is hypothetically proved that as a linguistic vehicle, the preposition over encodes 17 lexical concepts with unique semantic and formal selectional tendencies.